Learning from the new Higgs-like scalar before it vanishes - Bauer, Martin; Butter, Anja; González Fraile, Juan; Plehn, Tilman (Arxiv, 2017)
Motivated by a di-photon anomaly observed by ATLAS and CMS we develop an SFitter analysis for a combined electroweak-Higgs sector, and a scalar portal at the LHC. The theoretical description is based on the linear effective Lagrangian for the Higgs and gauge fields, combined with an additional singlet scalar. The key feature is the extraction of reliable information on the portal structure of the combined scalar potential. For the specific di-photon anomaly we find that the new state might well form such a Higgs portal. To obtain more conclusive results we define and test the connection of the Wilson coefficients in the Higgs and heavy scalar sectors, as suggested by a portal setup.
Gesehen am 10.01.2018